ANALISIS TEKNOLOGI LABORATORIS GERABAH DARI SITUS LERAN - Fadhlan S. Intan (BRIN, 2003)
In general, pottery from the Leran Site, Gresik, East Java, is included in the category of pottery with a fairly good quality, with the discovery of mafic minerals and felsic minerals, which greatly affect the color of the pottery. The low level of hardness (2-4 on the Mohs scale) is mostly caused by environmental factors where the pottery is found, which is in a watery environment, so that it affects the bonds between minerals, which in turn will affect the hardness level of the pottery.